Case report: Congenital multidrug-resistant tuberculosis - Zhang, Hongyi; Xia, Lu; Zhang, Peize (Frontiers in Tuberculosis, 2024)
Congenital multidrug-resistant tuberculosis (MDR-TB) is a rare disease with high mortality. We report a case of a neonate girl with congenital MDR-TB. The girl's mother underwent in vitro fertilization-embryo transfer (IVF-ET) and did not show any symptoms prior to delivery. After the 14th day of life (DOL), the girl had fever and worsening difficulty in breathing despite antibiotic treatment. She was then confirmed congenital MDR-TB and received ventilation and anti-TB treatment. When the girl's TB was diagnosed, her mother was screened for TB and found to have MDR-TB affecting both her lungs and reproductive system. They both recovered and were discharged from the hospital with anti-TB treatment ongoing.